Gastrointestinal symptomatology, diagnosis, and treatment history in patients with underweight avoidant/restrictive food intake disorder and anorexia nervosa: Impact on weight restoration in a meal‐based behavioral treatment program. Issue 6 (11th May 2021) - Cooper, Marita; Collison, Amira O.; Collica, Sarah C.; Pan, Isabella; Tamashiro, Kellie L.; Redgrave, Graham W.; Schreyer, Colleen C.; Guarda, Angela S.
Abstract: Objective: Gastrointestinal (GI) concerns are often presumed to complicate nutritional rehabilitation for restrictive eating disorders, yet their relationship to weight restoration outcomes is unclear. This retrospective chart review examined GI history and weight‐related discharge outcomes in primarily adult, underweight inpatients with anorexia nervosa (AN, N  = 107) or avoidant/restrictive food intake disorder (ARFID, N  = 22) treated in a meal‐based, behavioral eating disorder program. Method: Lifetime GI symptomatology, diagnoses, diagnostic tests, and procedures were abstracted from medical records. Generalized linear models examined associations of GI diagnoses, tests, and procedures with discharge BMI and rate of weight gain. Results: Ninety‐nine percent of patients reported GI symptomatology and 83% had one or more GI diagnoses; with constipation and GERD most common. GI diagnoses ( p <.01) and testing ( p <.001) were more common in ARFID than AN. Average inpatient weight gain (1.59 kg/week), and discharge BMI (18.5 kg/m 2 ), did not differ by group. Slower weight gain in patients with (1.3 kg/week), versus without (1.7 kg/week), history of tube feeding ( p  = .02), accounted for a main effect of GI procedures on inpatient rate of gain ( p  = .01). Discussion: Despite ubiquitous GI symptomatology, meal‐based weight restoration achieved average weekly weight gain above recommended APA guidelines for hospitalized patients with an eating disorder. History of tube feeding was associated with slower mean weight gain, which remained, however, within recommended APA guidelines.